2016
DOI: 10.1038/srep32514
|View full text |Cite
|
Sign up to set email alerts
|

Local and Circulating Endothelial Cells Undergo Endothelial to Mesenchymal Transition (EndMT) in Response to Musculoskeletal Injury

Abstract: Endothelial-to-mesenchymal transition (EndMT) has been implicated in a variety of aberrant wound healing conditions. However, unambiguous evidence of EndMT has been elusive due to limitations of in vitro experimental designs and animal models. In vitro experiments cannot account for the myriad ligands and cells which regulate differentiation, and in vivo tissue injury models may induce lineage-independent endothelial marker expression in mesenchymal cells. By using an inducible Cre model to mark mesenchymal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…In a recent study of ours, we demonstrated that musculoskeletal injury induces expression of CD31, VE-cadherin, and Tie2 in mesenchymal cells. Using cell transplantation assays, we also confirmed that endothelial cells isolated from uninjured muscle tissue undergoes in vivo endothelial mesenchymal transition when transplanted directly into the wound [65]. More recently, Olmsted-Davis et al found that the endoneurium played a key functional role in HO formation using Wnt1-CreERT for lineage tracing [39].…”
Section: Fluidity Of Cell Fate: Pathological Differentiationsupporting
confidence: 61%
“…In a recent study of ours, we demonstrated that musculoskeletal injury induces expression of CD31, VE-cadherin, and Tie2 in mesenchymal cells. Using cell transplantation assays, we also confirmed that endothelial cells isolated from uninjured muscle tissue undergoes in vivo endothelial mesenchymal transition when transplanted directly into the wound [65]. More recently, Olmsted-Davis et al found that the endoneurium played a key functional role in HO formation using Wnt1-CreERT for lineage tracing [39].…”
Section: Fluidity Of Cell Fate: Pathological Differentiationsupporting
confidence: 61%
“…Interestingly, using a VE-Cadherin-Cre driver, a recent report described the contribution of endothelial cells to HO following combined burn injury and tendonectomy[78]. Transplantation of endothelial cells isolated from the aorta or hindlimb musculature into the tendon injury site further suggested a potential, albeit minor, contribution of endothelium to tendon HO.…”
Section: Progenitors Of Heterotopic Ossificationmentioning
confidence: 99%
“…There are two commercially available VE-Cadherin-Cre strains (B6;129-Tg(Cdh5-cre)1Spe/J[79] and B6.Cg-Tg(Cdh5-cre)7Mlia/J[77]), each exhibiting highly efficient labeling of endothelium, but differential labeling of hematopoietic and other lineages. In comparing the studies of Wosczyna et al[65] and Agarwal et al[78], it is possible that different outcomes resulted from the use of different Cre drivers (not reported in ref. [78]).…”
Section: Progenitors Of Heterotopic Ossificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal cell phenotype is characterized by α-smooth muscle actin (α-SMA), N-cadherin, vimentin, type I collagen, fibronectin, and β-catenin. For further details, see text confined to epithelial cells but also occurs in endothelial cells, indicating that this process is crucial for tissue repair (Agarwal et al, 2016).…”
Section: Classification Of the Distinct Stages Of The Emt Processmentioning
confidence: 99%